PENGARUH TERAPI MUSIK KLASIK INSTRUMEN PIANO TERHADAP KUALITAS TIDUR PADA LANSIA DI PANTI WERDHA DAMAI RANOMUUT KOTA MANADO - Irwan Embang Walanda; Peekie Rondonuwu; Esterlita Mandagi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Abstract - Sleep quality in the elderly is a condition in which a person is unable to get adequate sleep, both in quality and quantity, with only short sleep or difficulty sleeping, generally 8-9 hours of good quality sleep normally. Classical music therapy, as well as the characteristics of classical music that cause relaxation in stress and blood pressure and muscles are classical music. The quantitative research method uses an experimental approach with one group pre-pest test design, with total sampling. There were 18 respondents who were elderly who lived in the Damai Ranoomut Nursing Home Manado. The study began April 2023. The results of the study using the Wilcoxon test obtained a significant value of 0.003, which is less than a = 0.05, meaning that there is an average difference between pretest and posttest, which means that there is an effect of classical piano music on improving sleep quality in the elderly. at the Damai Ranomut Werdha Home in 2023. According to research, this occurs due to the use/appropriate media in providing classical piano music therapy which is immediately played to the elderly 1 hour before going to bed.